2016
DOI: 10.1103/physrevlett.117.099902
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Spectroscopic Quadrupole Moments inSr96,98: Evidence for Shape Coexistence in Neutron-Rich Strontium Isotopes atN=

Abstract: This corrects the article DOI: 10.1103/PhysRevLett.116.022701.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 4 publications
7
38
0
Order By: Relevance
“…From Table I 2 ) value. Let us mention that the quality of the agreement between our results and the experimental data is similar to the one obtained recently using the 5D collective Hamiltonian approach based on the Gogny-D1S EDF [7].…”
supporting
confidence: 89%
See 4 more Smart Citations
“…From Table I 2 ) value. Let us mention that the quality of the agreement between our results and the experimental data is similar to the one obtained recently using the 5D collective Hamiltonian approach based on the Gogny-D1S EDF [7].…”
supporting
confidence: 89%
“…As a consequence of the subtle interplay between single-particle and collective degrees of freedom, nuclei in this region of the nuclear chart display a large variety of intriguing phenomena. Several experimental [2][3][4][5][6][7][8] and theoretical [9][10][11][12][13][14][15][16][17] studies have already been reported on the structure of those nuclei. In particular, the rapid structural change around the neutron number N = 60 has been carefully studied in Zr and Sr isotopes [2,7,12,14,15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations